RANCANG BANGUN SISTEM SIRKULASI HYDROGEN PADA PEM (PROTON EXCHANGE MEMBRANE ) FUEL CELL - Bernardino Yudika Soesanto; Waru Djuriatno; Eka Maulana (Jurnal Mahasiswa TEUB, 2023)
A fuel cell is a device that can generate electricity using environmentally friendly fuel. It produces electricity through a chemical reaction between hydrogen and oxygen, with water and electricity as the outputs. Due to its ability to produce water and electricity, fuel cells are considered environmentally friendly devices. However, fuel cells also have some drawbacks, such as the requirement for a balanced ratio of hydrogen and oxygen, the need for precise temperature control, and the disposal of unused hydrogen gas into the environment. This results in wastage of hydrogen gas, which could be recycled for further processing. A hydrogen circulation system is designed to recycle hydrogen gas, allowing it to be reused by the fuel cell. The research involves the use of an air filter to clean the hydrogen gas, ensuring that only gas is processed. Additionally, a recirculation pump is utilized to push the processed hydrogen gas back into the fuel cell's input. Keywords: Fuel Cell, Circulation System, Air Filter, Recirculation Pump